Contabilidade pública em adequação as Normas Internacionais - Baptista, Sandra Cabral (2014)
This work aims to present the main difficulties faced by accounting professionals working in the public sector in relation to the changes that has suffered due to the convergence offered by the harmonization of International Accounting Standards (IPSAS), as also by the Brazilian Accounting Standards applied to the Public Sector (NBCASP), and demonstrate the management of public resources and public assets. And yet, show why the creation of the Municipal Pension Institute, which brought benefits to the municipality as well as the actual servers, and know a little your assets and if there is a control that the institute has. To do so, we carried out an exploratory research, addressing the problem qualitatively, seeking to bibliographic data, and by performing interviews with the Former Executive Director, the current Director and the accounting service provider. However, it was noted that the creation of the Institute was feasible, they apply to employer contributions to benefit the server, reducing the costs of the federal entity, moreover, it was also noted that accounting for it is a very broad area is a dire need to be constantly updated, enabling the implementation and use of standards efficiently and effectively, thus presenting with clarity, transparency and accuracy all factors that affect the public patrimony.